Mathematical Modeling of Cylindrical Adapter Dynamics under the Action of Local Momentary Loads - Lugovoi, P.Z.; Sirenko, V.N.; Skosarenko, Yu.V.; Batutina, T.Ya. (Science and Innovation, 2024)
Methods and computing program to determine displacements and accelerations of points of the cylindrical shell (adapter) middle surface under the action of local momentary loads have been developed. Effect of local load on the oscillation parameters and deformation of the shell (adapter) has been studied by test example. The displacement and acceleration under the action of local momentary load have been established to be localized in the action points. The designed methods can apply to initial calculations of the parameters of oscillations and deformations of cylindrical shell (adapter) structural elements undergoing the action of heavy local momentary loads in the course of operation.